EVALUASI KUALITAS AIR PADA SISTEM PENGELOLAAN AIR BERSIH BERBASIS MASYARAKAT DI KECAMATAN BUKIT KAB. BENER MERIAH - Lismawati; Aulia Rohendi; Adian Aristia Anas (Program Studi Teknik Lingkungan Fakultas Sains dan Teknologi UIN Ar-Raniry Banda Aceh, 2021)
The unavailability of drinking water supply system, made the community set up a community-based clean water management system independently. The purpose of the study is the to determine the existing conditions in two community-based clean water supply systems at the Bukit District and to determine water quality in terms Regulation of the Minister of Health of Rebublic of Indonesia No 32 of 2017. The method used in this study are field including collecting water sample which will be analyzed in Laboratorium of UPTD Center For Health Laboratorium and Healty Equipment Testing, besides interviews with the authority. The research location is the villages of Bale Atu and Hakim Tunggul Naru. The parameters tested are physical (odor, taste, temperature, turbidity, dissolved solid), chemical (pH, iron, fluoride, cadmium, hardness, chloride, manganese, zinc, cyanide, lead and organic matter) and biological cell (Total Coliform and Escherichia coli), which are taken from eigth sampling point. The results physical and chemical parameters are in accordance with the Regulation of the Minister of Health of Rebublic of Indonesia. Biological parameters in the intake point of Bale Atu village were not found to contain Total Coliform and Escherichia coli, while at the intake point of Hakim Tunggul Naru there were Escherichia coli bacteria. To improve the community-based clean water supply system at Bukit District, a treatment disinfection treatment using chlor 36 kg/day is recommended.